Periodontal research contributions to basic sciences: From cell communication and host-parasite interactions to inflammation and bone biology - de Molon, Rafael Scaf [UNESP]; de Avila, Erica Dorigatti [UNESP]; Cirelli, Joni Augusto [UNESP]; Steffens, Joao Paulo (Tech Science Press, 2022)
The periodontium comprises all structures surrounding the teeth, including gingiva, root cementum, periodontal ligament and alveolar bone. Those tissues aim to protect and support the teeth and are challenged by a residing microbiota that leads to subclinical inflammation even in physiological conditions. Periodontitis, a prevalent multicausal inflammatory and destructive disease, develops as a result from complex host-parasite interactions. This unique physiologic and pathologic scenario enables the development of research methods which allows conclusions beyond the simple understanding of periodontal homeostasis. The aim of this viewpoint was to explore potential contributions of periodontal research to a wide array of basic science specialties, such as cell and molecular biology, microbiology, immunology, endocrinology, rheumatology, among others.
Keywords: Alveolar bone; Bone; Periodontal disease; Rheumatoid arthritis